Effective Suppression of Methane Emission by 2-Bromoethanesulfonate during Rice Cultivation. - Tatoba R Waghmode; Md Mozammel Haque; Sang Yoon Kim; Pil Joo Kim (PLoS ONE, 2015)
2-bromoethanesulfonate (BES) is a structural analogue of coenzyme M (Co-M) and potent inhibitor of methanogenesis. Several studies confirmed, BES can inhibit CH4 prodcution in rice soil, but the suppressing effectiveness of BES application on CH4 emission under rice cultivation has not been studied. In this pot experiment, different levels of BES (0, 20, 40 and 80 mg kg-1) were applied to study its effect on CH4 emission and plant growth during rice cultivation. Application of BES effectively suppressed CH4 emission when compared with control soil during rice cultivation. The CH4 emission rates were significantly (P<0.001) decreased by BES application possibly due to significant (P<0.001) reduction of methnaogenic biomarkers like Co-M concentration and mcrA gene copy number (i.e. methanogenic abunadance). BES significantly (P<0.001) reduced methanogen activity, while it did not affect soil dehydrogenase activity during rice cultivation. A rice plant growth and yield parameters were not affected by BES application. The maximum CH4 reduction (49% reduction over control) was found at 80 mg kg-1 BES application during rice cultivation. It is, therefore, concluded that BES could be a suitable soil amendment for reducing CH4 emission without affecting rice plant growth and productivity during rice cultivation.